CH2(PPh2=NSiMe3)(PPh2=S) and CH(PPh2=NSiMe3)(Ph2P=S)– as Ligands in Zinc Chemistry: Synthesis and Structures1. Issue 27 (10th July 2013) - Kuzdrowska, Magdalena; Murugesapandian, Balasubramanian; Hartenstein, Larissa; Gamer, Michael T.; Arleth, Nicholas; Blechert, Siegfried; Roesky, Peter W.
Abstract: The (iminophosphoranyl)(thiophosphoranyl)methane zinc complexes [(PPh2 =NSiMe3 )(PPh2 =S)CH2 ZnX2 ] (X = Cl, I) have been obtained by the reaction of CH2 (PPh2 =NSiMe3 )(PPh2 =S) with the corresponding zinc dihalides ZnCl2 and ZnI2 . The (iminophosphoranyl)(thiophosphoranyl)methane ligand coordinates as a bidentate ligand through the nitrogen and sulfur atoms to the zinc atom to form a six‐membered metallacycle (N–P–C–P–S–Zn). The reaction of CH2 (PPh2 =NSiMe3 )(PPh2 =S) with [ZnN(SiMe3 )2 2 ] and ZnPh2 resulted in the (iminophosphoranyl)(thiophosphoranyl)methanide complexes [(PPh2 =NSiMe3 )(PPh2 =S)CHZnN(SiMe3 )2 ] and [(PPh2 =NSiMe3 )(PPh2 =S)CHZnPh], respectively. In addition to the coordination of the phosphinimine nitrogen and sulfur atoms to the zinc atom, a long contact between the methine carbon atom of the P–C–P bridge and the zinc atom was observed in these complexes. The solid‐state structures of all the new compounds were established by single‐crystal X‐ray diffraction. Abstract : [(PPh2 =NSiMe3 )(PPh2 =S)CH2 ZnX2 ] (X = Cl, I), [(PPh2 =NSiMe3 )(PPh2 =S)CHZnN(SiMe3 )2 ], and [(PPh2 =NSiMe3 )(PPh2 =S)CHZnPh] have been synthesized and structurally characterized.